Assessment of perioperative anxiety levels at three time-points during hospital stay in patients undergoing elective surgery - Priya Goyal; Prisha; Joshua S. Chacko; Aman Goyal; Shikha Gupta; Suneet Kathuria (Perioperative Medicine)
Abstract Background Perioperative anxiety is associated with complications during and after surgery, resulting in prolonged hospital stays, and long-term physical and cognitive decline. A prospective observational study was conducted to assess anxiety levels at three time-points and identify sociodemographic factors influencing it. Methodology Three assessments were conducted on 105 patients (18–65 years) undergoing elective surgery after informed consent: A1 (day before surgery) using the State-Trait Anxiety Inventory (STAI-Trait) form, STAI-State form, and demographic data collection; A2 (on the day of surgery) with the STAI-S2 form; and A3 (24 h post-surgery) with the STAI-S3 form and a questionnaire on information requirements and pain. Results Average state anxiety scores were S2 (18.06) > S1 (17.55) > S3 (16.38). The primary concerns were fear of feeling pain after surgery (41%), fear of the results of the surgery(33.3%), and concerns about family (32.40%). Unmarried individuals had significantly higher anxiety scores than married individuals in S1 (20.80 vs. 16.79, p − 0.009) and S2 (23.10 vs. 16.87, p − 0.001). Females consistently scored higher than males, with a significant difference in S2 (19.51 vs. 16.79, p − 0.05). Patients with a medical history showed the highest anxiety in S3 (18 vs. 15.67, p − 0.037). Skilled workers displayed the highest anxiety levels in S1 (20.20) and S2 (22.40, p − 0.044) as compared to other groups, while professionals showed the highest anxiety in S3 (18.05). Females (33%), rurals (29%), and ≤ 8th-grade education group (54.5%) were significantly more likely to report receiving inadequate information about surgery compared to males (12.5%, p − 0.018), urbans (13%, p − 0.036), and higher education group (18%, p − 0.022). Younger individuals of < 30 years (47%) were more likely to feel that more information about surgery would have relaxed them compared to 41–50 age group (7.14%, p − 0.016). Conclusion The anxiety levels fluctuated over three time-points and were influenced by demographic, cultural, and psychological factors. Therefore, anxiety should be identified both preoperatively and postoperatively through an individualized approach. Additionally, a significant proportion of the population still requires more information, and the diverse informational needs across the groups underscore the necessity for individualized interviews to ascertain specific information requirements, thereby preventing any paradoxical increase in anxiety due to inappropriate information delivery.